P38 MAPK Activation In Myocardial Ischaemia - S. KUMPHUNE, PhD (International Journal of Pharma and Bio Sciences, 2011)
Ischaemic heart disease remains, and is likely to continue to be, the leading life threatening disease around the world. Signaling pathways have become more interesting as novel therapeutic targets in ischaemic heart disease. However, one needs to be very careful in picking the therapeutic target as one signaling molecule can activate and also cross-talk with other kinases. The activation of the p38-MAPK during myocardial ischaemia aggravates lethal injury. Recent evidences suggested the mechanism of p38-MAPK activation may differ by circumstances. Determining the precise mechanisms is crucial since it may allow prevention of the detrimental, but not the beneficial, and lead to the identification of the relevant downstream signals. Therefore, p38 MAPK may be a viable clinical target and form the basis of future studies designed to further dissect the signaling pathways and discover the downstream substrates will become hopes as a new frontier of therapeutic approach in ischaemic heart diseases.